Sustainable Tourism as an Economic Development Model in Evaluation and Prospects of Priority Tourism Destination Development Policy in Indonesia - Zakaria, Junaiddin (Jurnal Manajemen Pelayanan Publik, 2024)
The research evaluates the impact of policies on developing priority tourism destinations in Indonesia, focusing on sustainability within the tourism industry. The study aims to assess policy effectiveness, influence on local economic growth, and potential for sustainable tourism development in Indonesia. Qualitative methodology and QDAS software were used to analyze data, evaluating past initiatives to understand achievements and shortcomings. The study's findings demonstrate that assessing the effectiveness of policies aimed at developing priority tourism destinations can reveal both the accomplishments and shortcomings of past initiatives. Additionally, this evaluation can enhance our comprehension of how tourism can effectively contribute to the economic advancement of local communities. The study provides valuable guidance for policymakers in Indonesia to create more efficient and enduring tourist development strategies, emphasizing sustainable tourism as a key driver of economic growth.